Age-related determinants of the metabolic syndrome in women of reproductive age of the main ethnic groups of the Baikal Region - L. V. Belenkaia; L. V. Suturina; M. A. Darenskaya; A. V. Atalyan; L. M. Lazareva; Ia. G. Nadelyaeva; N. I. Babaeva; L. F. Sholokhov; L. I. Kolesnikova (Acta Biomedica Scientifica, 2023)
The aim of the study. To determine the age limit of the initial manifestations of the metabolic syndrome in women of reproductive age of the Caucasian and Asian ethnic groups. Materials and methods. The study included women of reproductive age of the Russian and Buryat ethnic groups (n = 1231). We carried out general clinical examination, studied glycemia levels and lipid metabolism indicators. The analysis of the components of the metabolic syndrome was performed taking into account age characteristics and ethnicity. Threshold values for the age of metabolic disorders manifestation were determined. Results. It was found that the main components of the metabolic syndrome in women of reproductive age of the Russian and Buryat ethnic groups were a decrease in  high-density lipoprotein (HDL), an increase in waist circumference, and an increase in blood pressure. The age-related determinants of the metabolic syndrome in the  population of women of reproductive age in the Baikal region were determined. It was shown that the age-related determinants of the metabolic syndrome in Caucasian and Asian women do not differ significantly and amount to 33.5 years (95% confidence interval (95% CI): 32.5; 38.5) and 36.5 years (95% CI: 27.5; 52.5), respectively. A universal critical age value was determined as 34.5 years (95% CI: 32.5; 38.5), which is associated with a significant increase in the prevalence of the metabolic syndrome in accordance with the ATP  III criteria. The ranking of metabolic syndrome criteria in the studied groups revealed the following order of their occurrence: the decrease in HDL index prevailed, followed by the increase in waist circumference, blood pressure, glucose and triglycerides; no dependence on the ethnicity was found. Conclusion. When assessing the age-related determinants of the metabolic syndrome in the mixed Caucasoid-Asian group, it is advisable to use universal approaches, taking into account the cut-off point of age, which is 34.5 years. The determination of age criteria for the correct classification of patients with respect to the manifestations of the metabolic syndrome is necessary to analyze the contribution of the age factor to the implementation of various metabolic syndrome predictors, to  develop prognostic models, and to  use effective age-determined markers of metabolic disorders.